Moderate tea consumption and dementia-related neuroimaging markers - Jin, Ting; Lu, Dongwei; Chen, Jiyu; Zhao, Wenxuan; Zhang, Yanfang; Zhang, Qing; Ye, Xujun; Qin, Juanjuan (Frontiers in Neurology, 2025)
IntroductionTea consumption may be associated with a reduced risk of dementia. However, the association between tea consumption and dementia-related neuroimaging markers remains unclear.MethodsWe analyzed 438,078 dementia-free participants from the UK Biobank at baseline, including 38,584 with complete brain imaging data. Linear regression models assessed brain imaging, Cox proportional hazards models evaluated dementia risk, and logistic regression analyzed cognitive decline. All analyses were adjusted for covariates and stratified by sex and age.ResultsModerate tea consumption was positively associated with regional brain volumes, including gray matter volume in the anterior parahippocampal gyrus, cuneal cortex, and the frontal lobe. Daily consumption of 6-7 cups of tea was significantly negatively associated with volumes of white matter hyperintensity (WMH) and the anterior cingulate cortex (ACC). Additionally, a significant association with the anterior parahippocampal gyrus was observed only in males. We found tea consumption showed a non-linear (p for non-linear < 0.0001) association with dementia. The lowest risk of incident dementia at a daily consumption level of 4–5 cups of tea (fully adjusted HR 0.804, 95% CI 0.752, 0.861) compared to non-consumption, consistent with the neuroimaging findings. No association was observed with cognitive decline.ConclusionModerate tea consumption was associated with volumes in several brain regions and reduced risk of dementia. This study comprehensively demonstrates the consistent associations of moderate tea consumption with dementia risk and brain health, highlighting the potential benefits of moderate tea consumption in preventing dementia.